Application Research of Three-Dimensional Printing Technology and Three-Dimensional Computed Tomography in Segmentectomy - He, Ping; Wu, Wei; Li, Tongxin; Zhou, Yu; Wang, Dong; Fu, Yong; He, Wang; Xu, Jing; Wang, Runyuan; Wu, Yi (Frontiers in Surgery, 2022)
Background:To compare the application of the emerging 3D printing technology and 3D-CT in segmentectomy. And to explore the advantages of 3D printing technology in thoracoscopic segmentectomy. Methods: We collected the clinical data of 118 patients undergoing thoracoscopic segmentectomy from January 2019 to April 2021 at the Thoracic Surgery Department, the Dianjiang People’s Hospital of Chongqing and Southwest Hospital. Among them, 61 patients were in the 3D printing group and 57 patients were in the 3D-CT group respectively. The perioperative data of these two groups of patients were analyzed respectively. Results: There were no significant differences between the two groups in age, gender, tumor diameter, pathology, the preoperative complications of diabetes and heart disease. However, the patients with the complications of hypertension in the 3D printing group are significantly more than the 3D-CT group(P=0.003). Compared with the 3D-CT group, patients in the 3D printing group had significantly shorter operation time (162.7±47.0 vs. 190.3±56.9 min, P=0.006), less intraoperative fluid input (1158.5±290.2 vs. 1433.2±653.3, P=0.013), and less total intraoperative fluid output , including intraoperative blood loss, urine excretion, and other fluid loss. In addition, there were no statistically significant differences in intraoperative blood loss, 24h pleural fluid volume, 48h pleural fluid volume, postoperative chest tube duration, postoperative hospital stay and complications between the two groups of patients (P>0.05). Conclusions: In thoracoscopic segmentectomy, the application of 3D printing technology shortens the operation time, reduces intraoperative fluid input and output, guides the operation more safely and effectively, and has better clinical application value.